Local Anesthetics: Review of Pharmacological Considerations (Texas Journal of Medical Science, 2023)
Local anesthetics have an impressive history of efficacy and safety in medical and dental practice. Their use is not so regular, and the negative effects are so low, that providers can overlook a lot of their pharmacotherapeutic principles understandable. The purpose of this continuing education article is important for various local anesthesia formulas in current use. Local anesthetics inhibit nerve conduction by inhibiting the passage of sodium ions through channels or ionophores within neural membranes. Usually these channels are present at rest, during which access to sodium ions is prohibited. When the neuron is excited, the channel adopts an activated or open state, in which sodium ions spread to the cell and begin depolarization. After a sharp change in membrane voltage, the sodium channel adopts an inactive state, at which point the active transport mechanisms return sodium ions outward. After this repolarization, the canal receives a normal state of rest. Valuing these sodium channel States helps explain the privileged sensitivity of local anesthetics for different classes of neuronal fibers